Síntese e caracterização de nanopartículas magnéticas funcionalizadas com núcleo magnético de magnetita - Roberta Viana Ferreira (2009)
Magnetic nanoparticles coated with silica have been subjected of extensive, and, in many aspects, also intensive investigations because of their potential application in different technological fields, particularly in biomedicine. The drug delivery to the specific sites through the application of magnetic field have been studied for biomedicine applications and are very promising because can resolve many of the problems associated with systemic drug administration. This work was conceived and is being carried out in: (i) synthesis of the ferrimagnetic nanoparticles, specifically magnetite, (ii) coating these particles with tetraethyl orthosilicate (TEOS), (iii) drug incorporation in silica coated-magnetite and (iv) drug controlled release. The nanosized magnetite sample was prepared by the reduction - precipitation and the nanomagnetite particles were coated by the sol-gel method, based on the hydrolysis of tetraethyl orthosilicate (TEOS). The so obtained materials were characterized with powder X-ray diffraction (XRD), FTIR spectroscopy, saturation magnetization measurements 57Fe Mössbauer spectroscopy at room temperature, zeta potential and thermal analysis. The drugs incorporation tetracycline, hydrocortisone or paclitaxel were incorporated in the particle during the magnetite coating process. The amounts of drugs delivered were monitored by ultraviolet spectrophotometry in the tetracycline, hydrocortisone and palcitaxel wavelengths. The summation until the end of release was considered 100%. The efficiency incorporation was analyzed with FTIR spectroscopy, zeta potential and thermal analysis. The release profile was analysed for application of mathematical model Korsmeyer-Peppas.